Waterbirds from wetlands of the southeast of the Córdoba province, Argentina - Brandolin, Pablo Germán (2011)
We present a waterbird inventory corresponding to 66 wetlands in the southeast of the Province of Córdoba, Argentina. Sixty six waterbird species belonging to 16 families and eight orders were recorded. We report observations of 11 neartic migratory, seven partial migratory and one altitudinal migratory species. Records of Callonetta leucophrys, Pluvialis dominica and Limosa haemastica considered rare species for the region, were recorded in this study. Data of the relative abundance revealed 10 very abundant species, 16 abundant, 25 scarce and 12 rare, while the relative importance identified nine frequent species, 19 non-frequent and 35 occasional. This work enhances baseline knowledge of waterbirds to assist future studies in this highly threatened area with high biodiversity.